PENDAMPINGAN DAN PEMBINAAN ANALIS PASAR IKM GERABAH/ KERAMIK DI DESA MELIKAN KECAMATAN WEDI KABUPATEN KLATEN - Titik Purwanti; Agung N Jati; Oki Kuntaryanto; Syarifah Aini; Zuyina Luklukaningsih; Anna Febrianty; Anis Marjukah; Abdul Haris; Kun Ismawati; Endang Wulandari; Nawang Kalbuana (FAKULTAS EKONOMI UNIVERSITAS SURAKARTA, 2023)
Abstract The marketing of pottery is getting better because the successors of these SMEs are no longer stuttering technology, they have made sales through various social media, there are even young pottery entrepreneurs who have been able and concentrated on selling their pottery abroad, although the standard of pottery for export must meet the requirements and high standards, so it requires painstakingness as well as caution in its manufacture. The problems experienced by partners are 1) Melikan Village has the potential to develop pottery products, moreover pottery is one of Klaten's brand images (precisely Melikan Wedi village), how to prepare an effective marketing strategy, 2) Pottery in Melikan Village, Wedi District, still has potential and still exists, for that it needs to be supported how pottery marketing can be improved so as to accelerate growth, 3) how to make Melikan Wedi pottery SMEs able to compete with competitors. The objectives of this assistance and coaching are 1) to prepare an effective marketing strategy, 2) to accelerate growth, 3) to be able to compete with competitors. The methods applied to overcome partner problems are a) providing educational provision of mentoring, coaching training so that Melikan pottery SMIs are able to analyse their marketing, b) organising mentoring, training on better marketing methods to produce more effective marketing, c) providing training to pottery human resources in order to strengthen the human resources of Melikan pottery SMIs to be able to compete with other pottery competitors. The targets and outcomes achieved in this mentoring and coaching programme are to provide an identity as a pottery craftsman who is able to compete and continue to grow into a solid pottery SMI, provide direction and guidance to focus on pottery marketing analysis programmes and coaching of stakeholders as well as the effectiveness of pottery marketing. Keywords: Pottery, Tilted Round, Glaze, Melikan Village.